Effect of Ball Milling on Electrocatalytic Activity of Perovskite La0.6Sr0.4CoO3-δ Applied for Lithium Air Battery. Issue 2 (18th November 2015) - Lee, Jong Ju; Oh, Mi Young; Nahm, Kee Suk
Abstract : Perovskite La0.6 Sr0.4 CoO3-δ was ball milled (BM LSC 1000) at various time periods and the effect of ball milling on structural and electrochemical characteristics were investigated. As the ball milling time increased, the particle size decreased and the surface area increased. Upon prolonged ball milling up to 48 hours, however, the particle size and surface area got stabilized. HRTEM images revealed formation of crystal defects and dislocations that resulted in the structural change from single to polycrystalline structures due to ball milling. The BM LSC1000 exhibited better electrocatalytic activities on oxygen reduction and evolution reactions (ORR and OER) than non–ball milled LSC 1000. Amongst, 24 hours ball milled LSC 1000 performed better in ORR and OER catalytic reactions than other BM LSC 1000. It is considered that the superior catalytic activity is attributed to the structural change and the crystal defects created due to ball milling. When applied as air cathode catalyst, the Li air batteries also showed better performance for BM LSC 1000 samples than non–ball milled LSC 1000. Overall, the 24 hours BM LSC 1000 exhibited the best electrocatalytic performance in terms of ORR and OER as well as superior battery performance with high capacity and reversibility.